2019
DOI: 10.3390/catal9010077
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrodechlorination of Chlorophenols in a Continuous Flow Pd/CNT-Ni Foam Micro Reactor Using Formic Acid as a Hydrogen Source

Abstract: Catalytic hydrodechlorination (HDC) has been considered as a promising method for the treatment of wastewater containing chlorinated organic pollutants. A continuous flow Pd/carbon nanotube (CNT)-Ni foam micro reactor system was first developed for the rapid and highly efficient HDC with formic acid (FA) as a hydrogen source. This micro reactor system, exhibiting a higher catalytic activity of HDC than the conventional packed bed reactor, reduced the residence time and formic acid consumption significantly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Supporting information contains a literature survey on the hydrogen-transfer hydrodechlorination of 4-chlorophenol in liquid phase with additional references, [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] XRD patterns of γ-Al 2 O 3 support and its prepared catalysts, XPS spectra of the synthesized catalysts, HAADF-STEM images of fresh and spent Pt/γ-Al…”
Section: Supporting Information Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting information contains a literature survey on the hydrogen-transfer hydrodechlorination of 4-chlorophenol in liquid phase with additional references, [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] XRD patterns of γ-Al 2 O 3 support and its prepared catalysts, XPS spectra of the synthesized catalysts, HAADF-STEM images of fresh and spent Pt/γ-Al…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…Supporting information contains a literature survey on the hydrogen‐transfer hydrodechlorination of 4‐chlorophenol in liquid phase with additional references, [53–72] XRD patterns of γ‐Al 2 O 3 support and its prepared catalysts, XPS spectra of the synthesized catalysts, HAADF‐STEM images of fresh and spent Pt/γ‐Al 2 O 3 catalyst, SEM images and EDX‐spectra of Pt/γ‐Al 2 O 3 , Rh/γ‐Al 2 O 3 , Ru/γ‐Al 2 O 3 and Pt/γ‐Al 2 O 3 catalysts, GC chromatograms of starting materials, products and representative examples of some experiments.…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…To complete the synthesis of DFMMP from the given 3-chlorodifluoromethyl pyrazole (CDFMMP 5 ), efficient hydrodechlorination is required; however, previous research indicated its difficulty when utilizing the usual hydrogenation technologies due to the high resistance of the C(sp 3 )–Cl bond to reduction conditions. 8 As a useful method from the latest literature, Braun et al reported catalytic hydrogenation using Pd/C as a catalyst. This protocol provided the target DFMMP in 97% yield at 110 °C in the presence of K 2 CO 3 as a base, but a high hydrogen pressure of 11 bar (1.1 MPa) is required and this may be affected by the production of over-hydrogenation products in a small amount.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium-functionalized silica monoliths constituted the core of the reactor and performed well in promoting the reduction of cyclohexanone and other ketones and aldehydes using 2-butanol as the hydrogen donor. Important kinetic parameters and data on the reaction rates were the main output of this study.In the context of the treatment of wastewater containing chlorinated organic pollutants, a continuous flow process for hydrodechlorination of chlorophenols was reported [6]. The process relies on the use of a Pd/carbon nanotube (CNT)-Ni foam microreactor system and formic acid as the hydrogen source.…”
mentioning
confidence: 99%
“…In the context of the treatment of wastewater containing chlorinated organic pollutants, a continuous flow process for hydrodechlorination of chlorophenols was reported [6]. The process relies on the use of a Pd/carbon nanotube (CNT)-Ni foam microreactor system and formic acid as the hydrogen source.…”
mentioning
confidence: 99%